Perkembangan Terapi Farmakologis pada Gagal Jantung Akut Dekompensasi - Bistamy Muhammad Nursabur (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Background: Acute decompensated heart failure is a cardiac disease that manifested from a chronic heart failure or occurred as de novo. With its high prevalence, there are many developments and innovations regarding its pharmacological therapies.Methods: This article was written using the literature review method, involving 24 sources from english journals and a book as a result of literature searching from Google Scholar search engine.Discussion: Disturbance of neurohormonal control results in acute decompensated heart failure indicated by an abnormally increased fluid in blood plasma that manifest in many abnormalities regarding the heart and lungs. Sympathetic nervous systems, renin-angiotensin-aldosterone system, arginine vasopressin, and natriuretic peptide have increased in functions and concentrations that played roles in failure of neurohormonal control of heart. Besides, heart failure causes release of several molecules like adrenomedullin and cardiac troponin. Several pharmacological therapies developed as managements of acute decompensated heart failure, such as adrecizumab, sacubitril-valsartan, nitroxyl donor, and diuretics.Conclusion: Researches regarding pharmacological therapies to acute decompensated heart failure need to be continued to be done in finding new therapies and developing previously used therapies.Keywords: acute decompensated heart failure, therapy